Microbial photoinactivation by blue light: advances and therapeutic perspectives in infections caused by multidrug-resistant pathogens - Ruiz-Arellano, Romina R.; Araque, María del C. (International Journal of Research in Medical Sciences, 2025)
Blue light (400–470 nm) is emerging as a promising alternative to address the growing threat of antimicrobial resistance. Microbial inactivation by blue light is based on the production of reactive oxygen species (ROS), which are light-induced and mediated by photosensitizers, resulting in the destruction of microbial cells. The microbicidal efficacy of blue light against diverse pathogens has been demonstrated in in vitro and preclinical studies, achieving reductions in cell viability greater than 3 log10 in multidrug-resistant bacteria. Furthermore, blue light has been reported to be harmless to host cells, which has spurred the development of clinical treatments, as well as protocols for food preservation and environmental disinfection. However, variability in parameters such as wavelength, dose, and endogenous chromophores limits standardization for clinical use. Therefore, future research will need to focus on optimizing its use in clinical practice, considering not only the effect on microorganisms but also on the exposed tissue. This review presents an up-to-date analysis of the mechanisms of action, experimental evidence, and clinical applications of blue light, emphasizing its potential as an alternative or adjunctive therapy in controlling infections caused by multidrug-resistant pathogens.